1989
DOI: 10.1093/nar/17.11.4255
|View full text |Cite
|
Sign up to set email alerts
|

Comparative inhibition of rabbit globin mRNA translation by modified antisense oligodeoxynucleotides

Abstract: We have studied the translation of rabbit globin mRNA in cell free systems (reticulocyte lysate and wheat germ extract) and in microinjected Xenopus oocytes in the presence of anti-sense oligodeoxynucleotides. Results obtained with the unmodified all-oxygen compounds were compared with those obtained when phosphorothioate or alpha-DNA was used. In the wheat germ system a 17-mer sequence targeted to the coding region of beta-globin mRNA was specifically inhibitory when either the unmodified phosphodiester oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0
2

Year Published

1990
1990
2003
2003

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(115 citation statements)
references
References 49 publications
6
107
0
2
Order By: Relevance
“…Substitution of the phosphodiester backbone of native DNA with phosphorothioate moieties markedly augments resistance to nuclease digestion. 35,36 Phosphorothioates, however, have also been found to bind with high affinity to a large number of proteins 37,38 presumably the result of alterations in the presentation of negative charges. Without appropriate controls, sequence-independent effects caused by phosphorothioate chemistry can be mistakenly attributed to a true antisense effect.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of the phosphodiester backbone of native DNA with phosphorothioate moieties markedly augments resistance to nuclease digestion. 35,36 Phosphorothioates, however, have also been found to bind with high affinity to a large number of proteins 37,38 presumably the result of alterations in the presentation of negative charges. Without appropriate controls, sequence-independent effects caused by phosphorothioate chemistry can be mistakenly attributed to a true antisense effect.…”
Section: Discussionmentioning
confidence: 99%
“…Antisense oligonucleotides can block translation by an RNase-H-independent process if they are complementary to the 5' non coding region of the message or to the splice acceptor site (29,(31)(32)(33)(34). In contrast, if they are directed against the coding region the inhibition is RNase-H dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Oligodeoxynucleotides and their analogs cause both selective and non-selective inhibition of expression in cell-free systems (Ghosh et al 1991a, b). Inhibition of /3-globin expression in Xenopus oocytes was chosen to compare the efficacy of different oligo analogs while avoiding the problems of relative cellular uptake, since the globin mRNA and the oligos are injected (Cazenave et al 1989). The amount of 35S-methionine incorporated into f3-globin expressed in the presence of an antisense oligo was compared with a control, and it was found that a natural (P0) anti-f3-globin-17-mer was quite effective in inhibiting expression, but that the S-oligo was even more effective.…”
Section: Antisense Inhibitionmentioning
confidence: 99%